Pergeseran Peran Wanita yang Sudah Menikah dan Implikasinya Dalam Layanan Bimbingan dan Konseling - Lita Gustiana; Mudjiran Mudjiran; Yeni Karneli (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2018)
Nowadays the role of married women not only do household chores like cooking, parenting, serving her husband, but had a double role, even many who call as a triple role, namely the woman as wife and mother, as a family, and as a responsible breadwinner. This article seeks to explain about the problem of shifting the role of married women and the implications for guidance and counselling services. The shift of the role of women is affected by various factors, namely; perceptions, shifts in social, economic and cultural beliefs. These factors give rise to a varied impact, namely; pressure as a parent, marital pressures, lack of involvement as a wife, a lack of involvement as parents, and the question of the work which interfere with. The impact experienced by married woman implicates with guidance and counselling services so that counselors have the basic skills of empathy and appreciation for a productive professional relationship building on the client woman.